Osteopontin and Integrin αvβ3 Expression during the Implantation Window in IVF Patients with Elevated Serum Progesterone and Oestradiol Level - He, Z.; Ma, Y.; Li, L.; Liu, J.; Yang, H.; Chen, C.; Lin, N.; Bai, Y.; Ma, R.; Li, R.; Wu, Z.; Qiao, J. (Geburtshilfe und Frauenheilkunde, 2016)
Background: To explore whether endometrial receptivity is determined by osteopontin (OPN) and integrin αvβ3 expression in women with elevated serum progesterone (P) and/or oestradiol (E2) who are undergoing in vitro fertilisation (IVF). Methods: According to serum hormone levels on the day of HCG administration, 33 infertile women were divided into 3 groups: the high E2, high P, and high E2 and P groups. The control group included 11 fertile, healthy women. Endometrial biopsy was performed on ovulation day + 7 to + 8 for all study participants, and the mRNA and protein expression levels of OPN and integrin αvβ3 were analyzed. Result: No statistically significant differences regarding OPN and integrin αvβ3 expression were found between infertile patients in the high P, high E2, high E2 and P and control groups. There was no significant correlation between OPN and integrin αvβ3 staining intensity during the implantation window biopsy in any of the groups studied. Conclusion: Endometrial OPN and integrant αvβ3 expression/co-expression is not impaired during the window of implantation in patients with high P, high E2, or high E2 and P levels. The clinical value of assessing endometrial receptivity with OPN and integrin αvβ3 seems to be uncertain.
Keywords: endometrial receptivity; IVF; elevated hormone levels; osteopontin; integrin αvβ3